Malignant Peripheral Nerve Sheath Tumour in a Patient of Type 1 Neurofibromatosis - Sengupta, Amitava; Bandyopadhyay, Ankan; Jash, Debraj; Saha, Kaushik (Journal of Medicine, 2012)
Malignant peripheral nerve sheath tumours (MPNST) constitute a rare type of soft tissue sarcoma which arises from peripheral nerves or Schwann cells, perineural cells or fibroblasts. MPNST is a rare neoplasm affecting 1 in 1,00,000 population. Here we report a case of a 36 year old male who presented to us with an upper abdominal swelling for last 3 months. At first ,a diagnosis of type 1 neurofibromatosis type 1(NF-1) was made. Contrast enhanced CT scan abdomen and thorax revealed presence of a complex, heterogenous mass in upper abdomen with extension towards left hemithorax. Histopathological examination done from true cut biopsy specimen of the mass was suggestive of malignant peripheral nerve sheath tumour. Positivity of tumour cells on immunohistochemistry to S-100 established the diagnosis of MPNST in type 1 neurofibromatosis. In conclusion, it was a rare case of MPNST in a patient of NF-1. DOI: http://dx.doi.org/10.3329/jom.v13i2.12761 J Medicine 2012; 13 : 219-221